PEMBINAAN PERSIAPAN AKREDITASI RA PADA GURU RA LABSCHOL IAIS SAMBAS - Dewi Ferawati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This coaching activity ia carried out so that managers and teachers of the RA Labscgool IAIS Sambas institution are able to meet the standards in submitting RA labschool IAIS Sambas accreditation documents. The targers of this activity are 1) the institutin is able to analyze the document needed at the time of accreditation; 2) the institution is able to prepare accreditation documents; 3) institutions are able to apply for accreditation through the SISPENA application. The method used is coaching for a least one month to explain the documents related to the eight standars. The final stage is compiling the documents required for accreditation. This community service activity is able to provide a concrete picture regarding the ipmplementation of RA accreditation and its stages.